Analisis Strategi Digital Marketing Di Masa Pandemi Covid-19 - Anindya Khrisna Wardhani; Arina Nuraliza Romas (EXERO : Journal of Research in Business and Economics, 2021)
The Covid-19 pandemic has affected the global economy and environment. The main victims of the covid-19 outbreak are Micro Small and Medium Enterprises (MSMEs), especially in developing countries due to the limited use of digital technology. Digital marketing is a strategic step that can be done by MSMEs to market their products without having to violate health protocols. Research methods use qualitative methods with an analytical descriptive approach. Descriptive research by collecting data based on factors that support the object of research, while qualitative research deals with ideas, perceptions, opinions, beliefs of people to be researched and everything that cannot be measured by numbers. The results showed that the difference in marketing before the pandemic and during the pandemic lies in the use of the internet. Digital marketing has only been widely known by the public since the pandemic, but people's understanding of the use of digital marketing is still quite low and needs to be improved so that marketing is done more effectively and efficiently.